Child agency and therapy in primary school. Issue 4 (19th May 2022) - Cedar, L.; Coleman, A.; Haythorne, D.; Jones, P.; Mercieca, D.; Ramsden, E.
ABSTRACT: The article reports on, and analyses, qualitative research involving children's therapy in two primary school contexts in England. It aims to explore the potentials of how agency as a concept can contribute to a challenge to existing theory, research and ways of working concerning therapy in primary school contexts. The article addresses how this challenge can be theorised: drawing on a critical review of how the fields of health, therapy, education and child rights connect to concepts of agency. Themes within this review include different disciplinary paradigms of childhood; how concepts of agency relate to those of child rights and voice; how a field such as therapy, created around concepts of welfare, can shift to acknowledge the presence of a child rights framework; and the complexities of child agency in therapy within primary school contexts. Data are included from the authors' research projects that access children's views of their therapy and that engages with them through a questionnaire, a member checking group and as co-researchers into their experiences of therapy. The analysis of the data reveals the challenges, potentials and advantages of recognising and listening to children as 'active agents' and 'experts' in relation to their therapy.